Chemical Constituents and Biological Activities of Cassia Genus: Review - Safaa Hafez; Samir Othman; Haitham Ibrahim (Ain Shams University, 2019)
A review of chemical constituents and pharmacological activities of genus Cassia, Family Leguminosae has been presented. There are about 600 species of this genus distributed all around the world. Many of these species are still not investigated. Hence, an attempt is made to present a review on the phytochemical and biological studies of Cassia species that remain a potential source for new natural pharmacologically active components.